An American Reflects on the Windsor Report - Douglas, Ian T. (Journal of Anglican studies, 2005)
The Windsor Report of the Lambeth Commission on Communion was published in late 2004 and has been released with encouragement from the Archbishop of Canterbury that it be studied around the Anglican Communion. A ‘reception’ process has been established to solicit input and monitor discussion on the Windsor Report from across the Anglican Communion. This article is a reflection on the report from the perspective of an American Episcopalian missiologist and was offered as part of the ‘reception’ process. In a step-by-step examination of the contents of the Windsor Report, the reflection presents underlying currents, concerns and possibilities for the Anglican Communion arising from the Report. There is much of benefit in the Report while at the same time dissent is registered with some of its presuppositions and findings.